Decoding the inflammatory-osteogenic axis in ankylosing spondylitis: mechanisms, dysregulation, and emerging therapeutic interventions - Parvin, Afroza; Sharma, Ashish Ranjan; Hasan, Md. Ashraful; Sharma, Garima; Shawan, Mohammad Mahfuz Ali Khan; Seo, Eun Min; Hasan, Md. Mahmudul; Lee, Sang-Soo (Frontiers in Immunology, 2025)
Ankylosing spondylitis (AS) is a chronic autoimmune disorder that primarily affects young people. Although genetic and environmental factors have been implicated in the pathogenesis of AS, the etiology of this condition remains unclear. Observations indicate that individuals possessing the human leukocyte antigen (HLA)-B27 allele exhibit elevated risk factors, as any mutation within this gene could potentially result in the development of AS in the future. However, it is interesting to note that many AS patients do not carry this gene, inferring the involvement of other genetic and nongenetic factors in the development of the disease. As the exact mechanisms remain unknown, no target-specific treatments exist to cure AS. Nonetheless, some treatment regimens have been devised to alleviate AS symptoms. This review thoroughly examines the molecular mechanisms implicated in AS, encompassing insights into the significance of pivotal biomarkers, such as extracellular matrix metabolites, immune cell dynamics, gut microbiota interactions, the Wnt signaling pathway, and its inhibitors. Furthermore, a thorough evaluation of the different mouse models used in AS research has been reviewed, which is crucial for understanding disease pathways and assessing treatment methods. In addition, significant progress in developing effective treatment strategies for AS, along with drugs available for treatment and ongoing clinical trials, has been summarized. A comprehensive understanding of experimental mouse models, along with insights into molecular mechanisms and biomarkers for AS, could aid researchers and physicians in discovering new treatment strategies for this challenging condition.